Presence of brain pathology in deceased subjects with and without chronic obstructive pulmonary disease. (November 2015) - Cleutjens, Fiona AHM; Spruit, Martijn A; Beckervordersandforth, Jan; Franssen, Frits ME; Dijkstra, Jeanette B; Ponds, Rudolf WHM; Wouters, Emiel FM; Janssen, Daisy JA
Patients with chronic obstructive pulmonary disease (COPD) have extrapulmonary co-morbidities, such as cardiovascular disease, musculoskeletal wasting and neuropsychological conditions. To date, it remains unknown whether and to what extent COPD is associated with a higher prevalence of brain pathology. Therefore, the aim of this retrospective study was to compare the prevalence of neuropathological brain changes between deceased donors with and without COPD. Brain autopsy reports of age-matched donors with ( n = 89) and without COPD ( n = 89) from the Netherlands Brain Bank were assessed for demographics, cause of death, co-morbidities and brain pathology. The prevalence of degenerative brain changes was comparable for donors with and without COPD (50.6% vs. 61.8%, p > 0.05). Neoplastic brain changes were reported in a minority of the donors (5.6% vs. 10.1%, p > 0.05). After correction for cerebrovascular accident or cardiac cause of death and Charlson co-morbidity index score, the prevalence of vascular brain changes was higher among control versus COPD donors (27.0% vs. 11.2%, adjusted p = 0.013, odds ratio = 2.98). Brain autopsy reports of donors with and without COPD did not reveal differences in the presence of degenerative or neoplastic brain changes. Vascular brain changes were described more often in controls. Prospective studies including spirometry and structural and functional brain imaging should corroborate our findings.